2017
DOI: 10.5194/bg-2017-219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution of planktonic biogenic carbonate organisms in the Southern Ocean south of Australia: a baseline for ocean acidification impact assessment

Abstract: <p><strong>Abstract.</strong> The Southern Ocean provides a vital service by absorbing about one sixth of humankind's annual emissions of CO<sub>2</sub>. This comes with a cost – an increase in ocean acidity that is expected to have negative impacts on ocean ecosystems. The reduced ability of phytoplankton and zooplankton to precipitate carbonate shells is a clearly identified risk. The impact depends on the significance of the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Similar low levels of coccolithophores have been projected in the Southern Ocean in Gregg and Casey (2007) (very low coccolithophore chlorophyll a), Krumhardt et al (2017) (growth rates at or close to zero which equates to low to zero CCPP) and Sinha et al (2010) (high nutrients resulting in coccolithophores being dominated by diatoms). For the Southern Ocean, it has been suggested that satellite PIC concentrations in subantarctic waters are overestimated by a factor of 2-3 while those in Antarctic waters may be even more so (Holligan et al,10 2010; Balch et al, 2011;Trull et al, 2018). The fact that three other global estimates, based on different sets of environmental parameters, all estimate very little productivity in the Southern Ocean seems to support this theory.…”
supporting
confidence: 55%
“…Similar low levels of coccolithophores have been projected in the Southern Ocean in Gregg and Casey (2007) (very low coccolithophore chlorophyll a), Krumhardt et al (2017) (growth rates at or close to zero which equates to low to zero CCPP) and Sinha et al (2010) (high nutrients resulting in coccolithophores being dominated by diatoms). For the Southern Ocean, it has been suggested that satellite PIC concentrations in subantarctic waters are overestimated by a factor of 2-3 while those in Antarctic waters may be even more so (Holligan et al,10 2010; Balch et al, 2011;Trull et al, 2018). The fact that three other global estimates, based on different sets of environmental parameters, all estimate very little productivity in the Southern Ocean seems to support this theory.…”
supporting
confidence: 55%
“…When the limits of species environmental ranges are not fully captured, this uncertainty can significantly impact the accuracy of SDM predictions (Hortal et al 2007, 2008, Rocchini et al 2011, Sánchez-Fernández et al 2011, Titeux et al 2017, El-Gabbas & Dormann 2018. It reduces the applicability of models for predictive purposes (Thuiller et al 2004), induces model overfitting (Tsoar et al 2007, Barve et al 2011, Guillaumot et al 2018b) and can lead to overestimating the extent of suitable areas (Anderson & Raza 2010). This bias can be partly overcome by reducing the extent of the projection area to the known distribution of the available occurrence records (Anderson & Raza 2010) and by increasing knowledge regarding species ecology and physiology in order to identify the environmental conditions that are unsuitable for their survival or development (Byrne et al 2016).…”
Section: Taxonomic Bias and Population Variabilitymentioning
confidence: 99%
“…Whenever possible, it is recommended to validate environmental data derived from satellite products at regional and local scales by comparing pixels on a satellite image with ‘real’ field observation data (Henson et al 2015, Trull et al 2018). Simple correlation analyses or more complex ground-truth processes are available to compare satellite and in situ data and to secure the interpretation of satellite-derived products (White-Newsome et al 2013, Allan 2014).…”
Section: Quality Of Datasetsmentioning
confidence: 99%
“…These waters would include the Austral Polar province (54) and to some extent, the Antarctic province (53). It has been reported that E. huxleyi abundance is typically low in the high latitude Southern Ocean (Charalampopoulou et al, 2016;Holligan et al, 2010) and other phenomena such as highly-reflective glacial flour or reflective loose ice could produce sufficient reflectance to adversely overestimate satellite PIC retrievals in this specific region (Balch et al, 2011;Balch, 2018;Trull et al, 2018). High latitude Phaeocystis blooms might also abnormally elevate the reflectance (Alvain et al, 2008).…”
Section: Potential Influence Of Case II Coastal Waters On Pic Concentmentioning
confidence: 99%